Student attitudes toward the development of a residence hall activity program at the University of Wisconsin--La Crosse - Dresen, Lloyd A (My University, 1972)
The major purpose of this study was to assess the attitudes of residence hall students toward the development of a residence hall activity program at the University of Wisconsin-La Crosse. The study also attempted to discover whether student attitudes toward a residence hall activity program varied according to the students' academic classification, sex, and college of academic major. A twenty percent random sample of the total population of students living in ten residence halls were asked to complete a questionnaire regarding their attitudes toward the development of a residence hall activity program. The questionnaire was comprised of items concerning five segments involved in the development of a residence hall activity program. The five segments investigated were innovation of an activity program, administrative responsibility and implementation of an activity program, adequacy and use of present campus facilities for an activity program, general categories of activities designed for an activity program, and preference for specific activities in an activity program. An analysis of all items relating to each segment was conducted according to tallied percentages in order to determine student attitudes toward each of the five segments. The student attitudes found to exist toward the five segments involved in the development of a residence hall activity program were: 1. Students expressed positive attitudes toward Segment I, the innovation of an activity program. 2. Students expressed positive attitudes toward Segment II, the administrative responsibility and implementation of an activity program. 3. Students expressed negative attitudes toward Segment III, the adequacy and use of present campus facilities for an activity program. 4. Students expressed positive attitudes toward Segment IV, the general categories of activities designed for an activity program. 5. Students expressed positive attitudes toward Segment V, the preference for specific activities in an activity program. Although attitudes of the sub-groups remained consistent with the attitudinal pattern of the total student sample, an interpretation of the data indicated that student attitudes did vary according to academic classification of the resident, sex of the resident, and college of academic major of the resident.
Keywords: Student activities -- Wisconsin -- La Crosse.; University of Wisconsin-La Crosse -- Student housing.; University of Wisconsin-La Crosse -- Students -- Attitudes.